Highlighting the importance of multidisciplinary approach: A rare case of primary periurethral poorly differentiated carcinoma - Kallirhoe Kalinderi; Michail Kalinderis; Konstantinos Linos; Georgios Salpigidis; Evangelos Papanikolaou; Maria Chalkidou; Antonios Mykoniou; Nikolaos Flaris; Konstantinos Papazisis; Apostolos Athanasiadis; Ioannis Kalogiannidis (Elsevier, 2020)
Objective: Tumors in the periurethral area can be a rare clinical entity with many difficulties not only in the diagnosis, as well as in the treatment plan. Skene's gland adenocarcinoma accounts for less than 0.003% of all female urethral malignant neoplasms. Case report: This report describes an extremely rare case of woman with a poorly differentiated carcinoma arising from the periurethral glands. Conclusions: Reporting of such rare cases enhance the understanding of the biological behavior of such tumors and the best treatment plan as well. This case report highlights the need for multidisciplinary approach of such rare cases, the lack of experience for such cases and the fact that the optimal treatment plan is very critical for the best prognosis of these patients. Keywords: Periurethral mass, Carcinoma, Multidisciplinary